TINJAUAN PENERAPAN PUTUSAN HAKIM TAHUN 2017-2019 PERUSAKAN HUTAN UU NO.41 TAHUN 1999 DENGAN UU NO.18 TAHUN 2013 - Vivi Sundari; Rumondang Rumondang; Musa Gabriel Ginting; Samuel Bambang Syaputra Siagian (Prodi Ilmu Hukum, Universitas Teuku Umar, 2020)
This study aims to find out the differences and similarities about forest destruction, to assess the quality of Comparison of Criminal Acts of Forest Destruction According to Law No.41 of 1999 with Law No.18 of 2013. With the background of problems regarding criminal acts of forest destruction and the application of the law taken by the judge. The research method used in this study is a normative juridical approach and cases of criminal acts of forest destruction. Criminal acts in the forestry sector are regulated in Law No.41 of 1999 concerning Forestry and Law No.18 of 2013 concerning the Prevention and Eradication of Forest Destruction. Forest destruction is generally an activity that uses forest areas without a permit (illegitimate) were the forms of forest destruction such as illegal logging, forest encroachment, an acquaintance of flora and fauna originating from forest friends protected by the law. Keywords: Implementation, Judge's Decision, Criminal Acts, Forest Destruction